Ultrahigh flexoelectric effect of 3D interconnected porous polymers: modelling and verification. (June 2021) - Zhang, Mingyuan; Yan, Dongze; Wang, Jianxiang; Shao, Li-Hua
Abstract: Non-conductive materials like rubbers, plastics, ceramics, and even semiconductors have the property of flexoelectricity, which means that they can generate electricity when bent and twisted. However, an irregular shape or a peculiar load has been the necessary condition to realize flexoelectricity, and the weight and deformability specific ratios of flexoelectricity of solids are limited. In this work, we develop a theoretical model of flexoelectricity of three-dimensional interconnected porous materials. Compared to the solid materials, porous materials can exhibit flexoelectricity under arbitrary loading forms due to their complex microstructures, and the weight and deformability specific flexoelectric output is much higher than that of the solids. Then, we verify the model by measuring the flexoelectric response of polydimethylsiloxane (PDMS) and porous polyvinylidene fluoride (PVDF). The porous PDMS with 3D micron-scale interconnected structures exhibits two orders of magnitude higher weight and deformability specific flexoelectric output than that of the solid truncated pyramid PDMS. The flexoelectric signal is found to be linearly proportional to the applied strain, the microstructural size and the frequency. Finally, we apply the theory to a more practical bending sensor, and demonstrate its stable functioning and accurate response. Our model can be applied to other porous materials, and the results highlight the new potential of porous micro-structured materials with a significant flexoelectric effect in the fields of mechanical sensing, actuating, energy harvesting, and biomimetics as light-weight materials. Highlights: Theoretical models for flexoelectric effect of porous materials are established. The theory is verified by porous PDMS and porous PVDF materials. A bending sensor of porous PDMS based on flexoelectric effect is demonstrated.